Sexual dimorphism in Leptodactylus latinasus (Anura, Leptodactylidae): nasal capsule anatomy,morphometric characters and performance associated with burrowing behavior - Ponssa, María Laura (2012)
In anurans, the ability to burrow has been associated with the characteristics of external morphology, with modifications in the musculoskeletal system and even in some brain regions. Male Leptodactylus fuscus construct subterranean chambers with the snout, where the eggs are deposited and early larval stages develop. Leptodactylus latinasus, a member of the L. fuscus group, is a good model to test the relationship among digging behavior of males, sexual divergence in the morphology of the nasal region, cranial-dimensions, and performance as digger. The goal of this work is to provide a detailed morphological description of the olfactory region, which allows detecting sexually dimorphic characters, to evaluate sexual divergence with head dimension data, and to test whether differences exist in the digging performance of each sex. Our data do not clearly indicate sexual dimorphism in head size, nasal region morphology or digging performance that can be linked with the burrowing behavior. Thus, the only unequivocal sexually dimorphic character associated with the construction of the nuptial chamber by males would be the rigid, chisel-like snout, present exclusively in males.